Pengaruh Brand Attitude, Brand Trust, Brand Image, dan Brand Value Terhadap Brand Loyalty - Prya, Dekha; Prastyani, Desy (Journal of Comprehensive Science, 2024)
This study aims to analyze the factors that influence consumer behavior towards Pop Mie instant cup noodles in Jakarta and Tangerang, focusing on the variables Brand Attitude, Brand Trust, Brand Image, Brand Value, and Brand Loyalty. For the sample of this study using purposive sampling technique with a total of 200 respondents. This study is a deductive-quantitative study using the SEM (Structural Equation Model) method. This study examines the effect of Brand Attitude, Brand Trust, Brand Image, Brand Value, on Brand Loyalty. The results revealed that of the four variables tested, only two, namely Brand Image and Brand Value, had a significant effect on Brand Loyalty. While Brand Attitude and Brand Trust showed the opposite results. These results indicate the importance of the image and value perceived by Pop Mie consumers in forming loyalty to the brand.